Encapsulating peritoneal sclerosis in liver transplant - Gabriel Melki; Abdalla Mohamed; Mina Fransawy Alkomos; Alisa Farokhian; Sohail M. Chaudhry; Varun Patel; Walid J. Baddoura (University of São Paulo, 2021)
Encapsulating peritoneal sclerosis occurs due to chronic irritation of the peritoneal surface resulting in inflammation and fibrosis. Encapsulating peritoneal sclerosis usually occurs in patients requiring peritoneal dialysis (PD); however, it may also occur in liver transplant patients. The fibrosis in encapsulating peritoneal sclerosis could be severe enough to cause small bowel obstruction (SBO). Herein, we report a case of encapsulating peritoneal sclerosis secondary to liver transplantation that presented with SBO. The patient was started on Tamoxifen for encapsulating peritoneal sclerosis and evaluated at follow-up without any other intestinal obstruction episodes. This case demonstrates that encapsulating peritoneal sclerosis can occur as a liver transplant complication and present with small bowel obstruction.